Correlating the microstructure to mechanical properties and wear behavior of an accumulative back extruded Al-Mg2Si in-situ composite. (November 2017) - Ebrahimi, M.; Zarei-Hanzaki, A.; Abedi, H.R.; Azimi, M.; Mirjavadi, S.S.
Abstract: The present work was conducted to study the effects of microstructural evolutions on the mechanical and wear behavior of an accumulative back extruded aluminum-based in-situ composite. The mechanical fragmentation and thermal disintegration of the primary and secondary Mg2 Si particles were found as the main microstructural changes. For that reason, the particle interspacing was decreased, the sharp ends were modified, and the reinforcements were more uniformly distributed. Surprisingly, the wear loss was dramatically decreased in processed materials in comparison to the as-received one. Oxidation and delamination were identified as the dominant wear mechanisms. These were addressed considering the microstructural refinement, and the modification of reinforcing particles with regard to morphology (rod-like, wormy or dot-like), size and distribution. Graphical abstract: Highlights: The correlation of microstructure, mechanical and wear properties have been studied. Mechanical and tribological property have been improved through the ABE process. Oxidation and delamination introduce as main wear mechanisms in each conditions. Formation of the oxide tribolayer avoids the adhesive wear. Acceptable strength and ductility after 3-passes leads to better wear properties.